Revealing the structure and functionality of graphene oxide and reduced graphene oxide/pyrene carboxylic acid interfaces by correlative spectral and imaging analysis. Issue 24 (9th June 2017) - Zaharie-Butucel, D.; Potara, M.; Craciun, A. M.; Boukherroub, R.; Szunerits, S.; Astilean, S.
Abstract : Healing and charge transfer effects at chemically derived graphene interfaces revealed through correlative Raman and two-photon fluorescence lifetime imaging. Abstract : A high-end correlated spectral and imaging multianalysis, adapted for bidimensional systems, is presented here to analyze graphene oxide (GO) and reduced GO (rGO) modified with pyrene carboxylic acid (PCA). Confocal Raman mapping was used next to two-photon excited Fluorescence Lifetime Imaging Microscopy (FLIM) to characterize the distribution of PCA on GO and rGO and compared to UV-vis and X-ray Photoelectron Spectroscopy (XPS) analysis of the materials. Raman imaging clearly highlights the difference in the spatial distribution of PCA molecules on GO and rGO. Two-photon excited FLIM helped in gaining insight into the elusive phenomena and effects occurring at the GO–PCA interface level. Apart from the charge transfer effects from PCA molecules to GO, the GO structure depends on the molecular orientation and the spatial distribution of PCA molecules identified by different sp 2 network domains in Raman mapping. Heating of GO–PCA results in an enhancement of the sp 2 network presumably as the PCA aromatic core becomes fused into the GO nanosheets whilst enriching the resulting rGO nanosheets with carboxyl functionalities. This "healing" effect observed in rGO–PCA might be of high importance for applications using rGO–PCA matrices and interfaces in particular for electrical devices.